Synergistic nanostructure and heterointerface design propelled ultra-efficient in-situ self-transformation of zinc-ion battery cathodes with favorable kinetics. (March 2021) - Luo, Hao; Wang, Bo; Wu, Fangdong; Jian, Jiahuang; Yang, Kai; Jin, Fan; Cong, Bowen; Ning, Yu; Zhou, Yu; Wang, Dianlong; Liu, Huakun; Dou, Shixue
Abstract: In-situ self-transformation is proved to be an effective strategy to design high-performance cathodes for aqueous zinc-ion batteries (ZIBs). However, the inferior transformation efficiencies during phase transition limit its further application. Herein, a 3D spongy VO2 -graphene (VO2 -rG) precursor has been designed for achieving the ultra-efficient in-situ self-transformation process from VO2 -rG into multifaceted V2 O5 ·nH2 O-graphene composite (VOH-rG). Benefiting from the highly conductive heterointerfaces, rich reaction sites and numerous ions diffusion channels of VO2 -rG, almost 100% VO2 nanobelts are converted into VOH during the first charging with few side reactions, indicating a highly efficient transformation kinetics. This strategy enables structural modulation from micro-nano level to molecular level by integrating pre-inserted H2 O molecules and constructing 3D porous heterogeneous architecture into the VOH-rG cathode simultaneously, leading to fast and enduring Zn 2+ (de)intercalation kinetics. Consequently, the VOH-rG cathode exhibits high capacity of 466 mA h g −1 at 0.1 A g −1, superior rate performance (190 mA h g −1 even at 20 A g −1 ) and excellent cycling stability with 100% capacity retention over 5000 cycles. Moreover, the assembled VOH-rG//Zn flexible quasi-solid-state batteries also present impressive performance. Such an ultra-efficient in-situ self-transformation strategy would pave a new way to explore promising electrode materials for advanced energy storage. Graphical Abstract: Ultra-efficient in-situ self-transformation strategy propelled by synergistic nanostructure and heterointerface design is developed to construct a multifaceted V2 O5 ·nH2 O-graphene composite, which enables structural modulation from both micro-nano level and molecular level by integrating pre-inserted H2 O molecules and constructing 3D porous heterogeneous architecture into the VOH-rG cathode simultaneously, thus inducing fast and enduring Zn 2+ (de)intercalation kinetics. ga1 Highlights: Synergistic nanostructure and heterointerface engineering are proposed for zinc-ion battery cathodes. The proposed strategy enables structural modulation from micro-nano level to molecular level. A nearly 100% phase transition can be achieved with few side reactions in the first charge process. High capacity, superior rate performance and excellent cycling stability can be simultaneously achieved.